Analysis of the characteristics and components for the frailty syndrome in older adults from central Chile. The PIEI-ES study. (January 2019) - Palomo, Iván; Giacaman, Rodrigo A.; León, Soraya; Lobos, German; Bustamante, Miguel; Wehinger, Sergio; Tapia, Juan Carlos; Fuentes, Manuel; Alarcón, Marcelo; García, Francisco; Albala, Cecilia; Fuentes, Eduardo
Highlights: An increase in the prevalence of frailty was observed in people 80 years old and older, both in women and men. Using adjusted logistic regression, advanced frailty state was more likely to occur in subjects with cognitive impairment. Frailty may be related with cognitive functioning, educational level and nutritional status in older adults. Abstract: Objective: To determine the prevalence and to characterize frailty in elderly subjects in four urban provincial capitals and two rural communes from Maule Region in Chile. Design: Cross-sectional study. Participants: 1205 participants aged 65 and older. Methods: The dataset was obtained from the PIEI-ES Study. Frailty syndrome was determined according to the criteria proposed by Fried. Data collection included questionnaires. Results: The study sample included 1205 individuals, of which 68% were females. Mean age was 73 years. The overall prevalence of frailty was 24.6%. Increase prevalence of frailty was observed in people 80 years old and older, both in women and men. Using adjusted logistic regression, advanced frailty state was more likely to occur in subjects with cognitive impairment. Conclusion: This study provides evidence that frailty may be related with cognitive functioning, educational level and nutritional status in older adults.